Validation of the GSFQ, a Self-Administered Symptom Frequency Questionnaire for Patients with Gastroesophageal Reflux Disease - Pierre Paré; François Meyer; David Armstrong; Myron Pyzyk; Dan Pericak; Goeree Ron (Canadian Journal of Gastroenterology)
BACKGROUND: Although the diagnosis of gastroesophageal reflux disease (GERD) is based primarily on symptoms experienced by a patient, relatively little attention has been paid to the development and validation of self-administered questionnaires specific to GERD symptoms. The present article presents the validation of the short, self-administered GERD Symptom Frequency Questionnaire (GSFQ).